The Impact of Advanced Maternal Age on Neonatal Outcome in Preterm Births before 34 Weeks - Daniel Tairy; Ohad Gluck; Yakira Izaik; Jacob Bar; Eran Weiner; Giulia Barda (Clinical and Experimental Obstetrics & Gynecology)
Background: In recent years a trend towards childbearing at older maternal age is evident. Most of the current literature investigated the association between advanced maternal age and neonatal outcome at term. We aimed to study the outcomes of the mother and the neonate among preterm births of women of advanced maternal age. Methods: This retrospective study between 2009 to 2017, comprised 494 singleton preterm births between 24 and 34 weeks gestation, of which 116 (23%) were of 35 years old or older (advanced maternal age) and 378 (77%) were of younger women. The medical records were reviewed and the outcomes of the mother and the neonate were compared between advanced maternal age (≥35 years) and younger women. Results: The rate of severe intra-ventricular hemorrhage (IVH) and of composite adverse neonatal outcome was lower among advanced maternal age women compared to younger women (p = 0.02 and p = 0.05 respectively). In multivariate regression analysis, composite adverse neonatal outcome was found to be independently inversely associated only with advanced maternal age (adjusted odds ratio (aOR) 0.45 95% confidence interval (CI) 0.23–0.86). Conclusions: Advanced maternal age was not found to be a risk factor for adverse neonatal outcome among preterm births before 34 weeks, and might be a protective factor from early neonatal complications.